1998
DOI: 10.1381/096089298765555033
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adjustable Esophagogastric Banding: a Preliminary Experience

Abstract: Laparoscopic adjustable esophagogastric banding is a simpler and safer procedure than laparoscopic adjustable gastric banding. It also works as a very efficient anti-reflux procedure, at least in the short term. It appears to be equally efficient as a weight-reducing operation as gastric banding. Further follow-up of the patients involved is necessary in order to evaluate the results in the longer term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 5 publications
2
7
0
1
Order By: Relevance
“…Weight reduction is a little slower than in our series of vertical banded gastroplasty, but it progresses for a longer period [16]. Other series with a follow-up of >1 year have shown similar results, with a mean percentage of excess weight loss between 48 and 70% [5,8,9,12,13,15]. Interestingly, O'Brien recently showed that weight reduction can progress for up to 4 years after the initial rapid fall usually seen following bariatric surgery [13].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Weight reduction is a little slower than in our series of vertical banded gastroplasty, but it progresses for a longer period [16]. Other series with a follow-up of >1 year have shown similar results, with a mean percentage of excess weight loss between 48 and 70% [5,8,9,12,13,15]. Interestingly, O'Brien recently showed that weight reduction can progress for up to 4 years after the initial rapid fall usually seen following bariatric surgery [13].…”
Section: Discussionsupporting
confidence: 67%
“…Some authors have proposed a posterior fixation of the band [4]. Others stressed the importance of placing the band above the lesser sac [7], or even placing the band posteriorly at the esophagogastric junction [12]. We have modified our technique according to these reports and now place the band above the lesser sac.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these hypotheses however has been proven yet, although investigations from Forsell indicated a pouch enlargement of 7–8 times the initial size [21]. The results of our series, confirmed by other authors, were unsatisfactory [12, 17, 22]. To overcome these technical problems and improve the results the operation technique has been adjusted to a higher-positioned band above the lesser sac creating a smaller pouch of 10–15 cm 3 .…”
Section: Discussionsupporting
confidence: 55%
“…FSPD is considered to be a result from pouch dilatation [6, 8, 10, 11, 12, 13, 14, 15]and/or slipping of the posterior stomach wall through the band [8, 9, 10, 16, 17, 18, 19, 20]. Neither of these hypotheses however has been proven yet, although investigations from Forsell indicated a pouch enlargement of 7–8 times the initial size [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ó õ³ðóðã³÷í³é êë³í³ö³ Óêðà¿íñüêîãî íàóêîâî-ïðàêòè÷íîãî öåíòðó åíäîêðèííî¿ õ³ðóð㳿, òðàíñ-ïëàíòàö³¿ åíäîêðèííèõ îðãàí³â ³ òêàíèí ÌÎÇ Óê-ðà¿íè îïàíîâàíî òåõí³êó ëàïàðîñêîï³÷íîãî áàíäàaeóâàííÿ øëóíêà ñèñòåìîþ Làð-Band, çà-ïðîïîíîâàíó 1998 ðîêó äîêòîðîì E. Niville [5] òà íàçâàíó "øëóíêîâî-õàð÷îâèì áàíäàaeóâàí-íÿì". Õ³ðóðã³÷íå âòðó÷àííÿ âèêîíóºòüñÿ ÷åðåç ï'ÿòü ïîðò³â (â³äåîêàìåðà, 2 ðîáî÷³ ³íñòðóìåí-òè, ðåòðàêòîð äëÿ ïå÷³íêè òà çàòèñêà÷-ãðàñïåð äëÿ òðàêö³¿ øëóíêà).…”
Section: безпосередні та віддалені результати хірургічного лікування unclassified